ANALISIS KEBUTUHAN INFORMASI DAN UPAYA PEMENUHAN KEBUTUHAN INFORMASI KOMUNITAS TULI LANCANG KUNING (KUTILANG) PEKANBARU - Adinda, Rizka; Amelia, Vita; Sondra, Aivan (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
The article "Analysis of Information Needs and Efforts to Fulfill the Information Needs of the Lancang Kuning Deaf Community" aims to find out how information needs and efforts to provide information needs exist in the Lancang Kuning Deaf Community (KUTILANG) Pekanbaru. This research uses qualitative methods. The subjects in this research were members of the Pekanbaru Lancang Kuning Deaf Community (KUTILANG). Data collection used was interviews, observation and documentation. The results of this research are an identification of the various needs of members of the Lancang Kuning Deaf Community and efforts to provide their information needs. It can be seen that the information needs of the Lancang Kuning Deaf Community (KUTILANG) are still not met. The obstacles or difficulties experienced by deaf people result in the formation of the characteristics of the information they need. The efforts of the Lancang Kuning Deaf Community (KUTILANG) to meet their information needs include searching for information via gadgets or online and by reading the lips of the person they are talking to.